Zróżnicowanie ekstensji tekstowej fonetycznych form obocznych w Księgach o gospodarstwie z 1549 roku (oboczność biał- || białł- oraz wariantywność w zakresie kontynuantów grup *sŕ, *zŕ, *žŕ, *(s)tьc i *(z)dьc) - Osiewicz, Marek (Slavia Occidentalis, 2014)
A material basis for the study is the first Polish language edition of Księgi o gospodarstwie by Piotr Krescentyn from 1549 (Cracow, Helena Unglerowa). The study led to the formulation of the following conclusions: 1) the variancy biał- // białł- is most likely of Great Polish origin; 2) the variancy miestce // miesce confirmed in the prints from the 16th century has a graphical character motivated by technical factors (typesetting); 3) the distribution of the analysed phonetic variants in Księgi… is not equal; 4) the supreme degree of normalization of the studied variancies has been confirmed in the combinations R–Cc; 5) variant conditions, non-normalized, appeared in the parts: Cresc293–384 and CrescDd–[0]C; 6) a greater part of the textual space of the historical text–from the combination A to the combination Cc– reveals Great Polish features; the remaining part–the combination Dd–Ii and the initial chapters–reveal evident Little Polish features.